Karakteristik Migrasi dan Dampaknya terhadap Pengembangan Pedesaan Kecamatan Kedungjati, Kabupaten Grobogan - Rahmi, Aulisa; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Rural development can’t be separated from the socio-economic condition of the community and the community's ability to access available resources. Limitation access of resource has reduction rural job oppurtunity. Farm Families need to diversivication their livelihood, one through migration. This study aims to Assess District Kedungjati Migration Characteristics and Influence on Rural Development Kedungjati. The methods used in this research is quantitative data collection is done using questionnaires given to migrants/migrant families. This study has four goals of the analysis, the analysis of access to resources and employment; analysis of the characteristics of migration; analysis of migration patterns, and analysis of the use of remittances and their impact on rural development. In the analysis used descriptive quantitative analysis techniques. Results of this study states that the migration has different characteristics, so it is difficult to find general patterns. In Kedungjati, farmers are migrating because of three main reasons: first, the limited opportunities in the access to and utilization of resources, limited natural resources and the second as an attempt to secure revenue.